ANALISIS CEMARAN LOGAM BERAT MERKURI DALAM KRIM PEMUTIH WAJAH YANGBEREDAR DIPASAR TRADISIONAL DENGAN METODE SPEKTROFOTOMETRI SERAPANATOM - Anggraeni, Vina Juliana (Journal of Pharmacopolium, 2018)
Mercury is one of the most dangerous chemicals that is often added to whitening cream. There are many manufacturers or sellers of whitening cream who use mercury in their products even though it is use is prohibited. This research conducted a qualitative and quantitative analysis of mercury on five samples of whitening cream in the traditional market. Qualitative analysis was performed using  KI  reagent  and  showed  five  samples  containing  mercury.  Then,  the  determination of mercury in the sample by Atomic Absorption Spectrophotometer at a wavelength of 243,7 nm. From the validation result, the regression equation obtained from the calibration curve is Y = 0,016779x - 0,04377 with LOD and LOQ of 2,1552 µg/L and 7,184 µg/L. The accuracy test is indicated by the percent recovery is in the range 88-97% and the precision test is shown with the % RSD value of 0,044-1,57%. The quantitative analysis results of five samples showed that all samples contained mercury levels range from 51,576 ppm to 3886,776 ppm. Keywords:Whitening cream;Mercury;Atomic Absorption Spectrophotometer.